Handbook of HPLC - Corradini, Danilo; Phillips, Terry M. (Chromatographic science series, 2010)
Covering advancements in separation technique, this book presents concepts including monolithic columns, bonded stationary phases, micro-HPLC, two-dimensional comprehensive liquid chromatography, and capillary electromigration techniques. It covers areas of HPLC application, including chiral pharmaceutical, food, and forensic analysis